A Study on Breastfeeding Practices Among Mothers in Rural Area of Mangalore District: A Cross-Sectional Study - Shashank KJ; Chethan TK (Medsci Publications, 2016)
Backgrounds: The initial growth of a child depends upon the duration and frequency of breastfeeding it receives, since the breast milk provides important nutrients to infants and young children and protects them against certain infections and helps in the child survival. Materials and Methods : A community based Cross sectional study was conducted from May 2014 to August 2014 in therural fields practice ofK.S. hedge medical academy .A total of 278 houses from the list were visited. Data was Collected in pretested andSemi StructuredQuestionnaire by Interview technique. Results: The initiation of Breastfeeding was done within one hour by 37.4% .Only 89(29.5%) of the children were given prelacteal feeds in the form of honey, sugar water in our study.Nearly 213 (76.6%) of the mothers had fed colostrum to the newborn soon after delivery. Conclusion:Prelacteal feeds and colostrum was discarded by the majority of the primi parous mothers than multiparous mothers. Hence IEC activities should be enhanced so as to change the behaviour of 100% mothers for Initiation of breastfeeding at the earliest, exclusive breastfeeding and weaning practices.